Influence of varieties and growing seasons on the distribution of Botryodiplodia theobromae causing fruit rot disease of coconut - Ekhorutomwen, Osayomore Endurance; Chidi, Nnamdi Ifechukwude; Owoh, Ekaete Mary; Shittu, Olalekan Hakeem (International Journal of Sustainable Agricultural Research, 2024)
This study examines an intensive field survey on the fruit rot disease of coconut that was conducted between April 2021 and March 2023 to observe the distribution of Botryodiplodia theobromae causing the coconut fruit rot disease across varieties and growing seasons in 2 major coconut-growing areas in Ovia North-East Local Government Area, Edo State, Nigeria. Coconut (Cocos nucifera L.) is an important economic crop. Its production is affected by several factors; among them, diseases play a major role. The fruit rot disease of coconut is a disease frequently encountered by coconut farmers. Fruit rot disease incidence was recorded daily from coconut fields cultivated with four different coconut varieties. The study examined a total of 8764 coconut fruits from 32 coconut palms. The causal agent of fruit rot was isolated from the internal tissues of infected fruits using the direct plating technique in potato dextrose agar. The causal agent of the disease was identified as B. theobromae. The study found that the relative distribution of B. theobromae in the study area significantly explained the proportion of the disease distribution in coconut varieties across the growing seasons. The study reveals a high level of variability in the percentage of disease incidence (PDI) between coconut varieties and fruit rot. The distribution and/or relative abundance of B. theobromae causing the fruit rot disease of coconut is influenced by coconut varieties and growing seasons in the two coconut-growing areas examined in the study.